2008
DOI: 10.1523/jneurosci.0538-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

DOC2B Acts as a Calcium Switch and Enhances Vesicle Fusion

Abstract: Calcium-dependent exocytosis is regulated by a vast number of proteins. DOC2B is a synaptic protein that translocates to the plasma membrane (PM) after small elevations in intracellular calcium concentration. The aim of this study was to investigate the role of DOC2B in calcium-triggered exocytosis. Using biochemical and biophysical measurements, we demonstrate that the C2A domain of DOC2B interacts directly with the PM in a calcium-dependent manner. Using a combination of electrophysiological, morphological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
95
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(109 citation statements)
references
References 83 publications
14
95
0
Order By: Relevance
“…Such slow dissociation of the C2AB from ULV correlates with the time constants of asynchronous neurotransmitter release at the synapse [24] and with the contribution of DOC2B to asynchronous release phase [24,25] ] microdomains or may increase its affinity due to the vicinity of PLs head groups as suggested for other C 2 domains [8,12]. The finding that C2A can affect DOC2B interaction with the membrane is also supported from observations of DOC2B D218,220N , a DOC2B with mutations in C2A, found to be constitutively associated with the PM [1,23]. These previous data suggested that C2A serves as the primary DOC2B Ca 2+ sensor.…”
Section: + Dissociation Precedes C2ab-membrane Dissociationsupporting
confidence: 54%
See 3 more Smart Citations
“…Such slow dissociation of the C2AB from ULV correlates with the time constants of asynchronous neurotransmitter release at the synapse [24] and with the contribution of DOC2B to asynchronous release phase [24,25] ] microdomains or may increase its affinity due to the vicinity of PLs head groups as suggested for other C 2 domains [8,12]. The finding that C2A can affect DOC2B interaction with the membrane is also supported from observations of DOC2B D218,220N , a DOC2B with mutations in C2A, found to be constitutively associated with the PM [1,23]. These previous data suggested that C2A serves as the primary DOC2B Ca 2+ sensor.…”
Section: + Dissociation Precedes C2ab-membrane Dissociationsupporting
confidence: 54%
“…By interacting with membranes, SNARE proteins, and additional factors, DOC2B enhances spontaneous and asynchronous neurotransmitter release [1,6,[23][24][25]. Here, we structurally and biochemically analyzed the individual C 2 domains and the C2AB tandem to shed light on DOC2B's Ca 2 + -binding properties and the conformational and functional effects of Ca 2 + on DOC2B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They performed most of their experiments using a buffer without calcium (i.e., Nonidet P-40 lysis buffer). Since DOC2b has conserved Ca 2ϩ -binding sites and is thought to be a Ca 2ϩ sensor protein in other cell types such as neuron (32) and chromaffin cells (33), Ca 2ϩ might be important for the physiological properties of DOC2b in ␤-cells. Further work is required to uncover the underling mechanisms by which DOC2b regulates SNARE assembly in response to insulin.…”
Section: Doc2b Regulates Glut4 Vesicle Fusionmentioning
confidence: 99%